PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI ESTEH INDONESIA SUNGAI LIAT - Trimora, Doan Carlo (Media Mahardhika, 2024)
This research was conducted to determine how much impact product quality has on customer satisfaction at Esteh Indonesia Sungai liat and the impact of service quality on customer satisfaction at Esteh Indonesia Sungai Liat. The type of research used is quantitative research with an explanatory approach. The results obtained in this study are that the product quality variable has a significant effect on customer satisfaction with a regression coefficient value of 0.101, meaning that product quality has an influence on customer satisfaction of 0.101. Service quality has a significant effect on customer satisfaction with a regression coefficient value of 0.292, meaning that service quality has an influence on customer satisfaction of 0.292. Based on the results of this study, it is hoped that Esteh Indonesia Sungai Liat can improve the quality of the products used and provide faster and more responsive service quality to customers in order to increase customer satisfaction even more.